GERAKAN MASYARAKAT SEKOLAH TANGGAP BULLYING DALAM UPAYA PENCEGAHAN BULLYING PADA ANAK USIA SEKOLAH - Lestari, Nina Dwi; Hidayati, Laili Nur; Abadiyah, Salis Sangadatun (Uhamka Press, 2019)
The phenomenon of bullying is currently a serious problem, especially in groups of school-age children because the incidence has increased from year to year. The results of interviews with fourth and 5th-grade students at Bangunjiwo Elementary School showed that 80% of students had been involved in the incidence of bullying. The results of interviews with teachers indicate that teachers have not known much about the problem of bullying. So far there is no school policy in the effort to prevent and overcome bullying. The data shows that the teacher's perception of bullying in school-age children is still not right. This community service program aims to improve the knowledge, awareness, and ability of the school community in efforts to prevent bullying in school-age children by increasing the participation of the school community. This program is carried out through tiered education for students, teachers, employees, student principals regarding bullying in school-age children, counseling training and mentoring for teachers, policy advocacy efforts related to bullying and the creation of health promotion media related to bullying. The resulting output in the form of increased knowledge, attitudes and perceptions of partners related to bullying in school-age children and the initiation of school policies in the prevention of bullying.